Biotransformation of vinblastine to vincristine by the endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Ahmad, Absar (Biocatalysis and Biotransformation, 2013)
A fungal transformation method for the production of the less abundant but more valuable anticancer drug vincristine using the more abundant anticancer drug vinblastine by an endophytic fungus Fusarium oxysporum isolated from the plant Catharanthus roseus is described. Vinblastine dissolved in sterile water when incubated with the fungal mycelial mass was transformed into vincristine at room temperature. The biotransformation process was monitored by periodic sampling of aliquots that were extracted with ethyl acetate. The crude transformed compounds were analysed using TLC where the Rf value of the spot obtained on the 8th day was found to be similar to that of standard vincristine (Rf 0.74). Purification by HPLC using a C 18 symmetry column showed a peak with RT (34.9 min) similar to that of standard vincristine. Further characterization with the help of ESI-MS showed a peak at m/z 825 attributed to the (M + H)(+) ion. This indicated that the fungus Fusarium oxysporum had converted vinblastine to vincristine.
Keywords: Biotransformation; endophytes; fusarium oxysporum; Vinblastine; vincristine